2008
DOI: 10.1111/j.1439-0310.2007.01443.x
|View full text |Cite
|
Sign up to set email alerts
|

Canine Reconciliation and Third‐Party‐Initiated Postconflict Affiliation: Do Peacemaking Social Mechanisms in Dogs Rival Those of Higher Primates?

Abstract: Conflicts over food, access to mates, or other limited resources can sometimes escalate into aggression. In species that form social groups, these aggressive conflicts can jeopardize the benefits of group living, such as enhanced access to valued resources, necessitating the development of behavioural mechanisms that either mitigate conflicts, prevent aggressive escalation or resolve disputes. Two important mechanisms for managing the effects of disputes involve postconflict (PC) affiliative behaviour, either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 39 publications
(70 reference statements)
2
102
2
2
Order By: Relevance
“…32,33,[60][61][62][63][64][65] Moreover, the stressalleviating effect of reconciliation in human children assessed using levels of self-directed behavior 64 has now been confirmed based on analysis of salivary cortisol levels. 8 As the evidence for the stress Canis domesticus Versele-Laga, Deinze, Belgium 26 Corvus frugilegus* University of Cambridge 27 Strengthen partner bonds † Functions are in italics if they were tested in the study. Cells are empty for cases where no function was suggested.…”
Section: Opponent Relationship Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…32,33,[60][61][62][63][64][65] Moreover, the stressalleviating effect of reconciliation in human children assessed using levels of self-directed behavior 64 has now been confirmed based on analysis of salivary cortisol levels. 8 As the evidence for the stress Canis domesticus Versele-Laga, Deinze, Belgium 26 Corvus frugilegus* University of Cambridge 27 Strengthen partner bonds † Functions are in italics if they were tested in the study. Cells are empty for cases where no function was suggested.…”
Section: Opponent Relationship Repairmentioning
confidence: 99%
“…7,10 The majority of research on post-conflict behavior has focused on reconciliation, the affiliative post-conflict interaction between former opponents, 11,12 but important post-conflict interactions may also occur between the opponents and bystanders uninvolved in the previous conflict. 13,14 In particular, a number of recent studies have demonstrated the phenomenon of post-conflict affiliation directed from a bystander to the recipient of aggression in a variety of species from primates [15][16][17][18][19][20][21][22][23][24][25] to dogs 26 and rooks. 27 This review focuses on bystander to recipient interactions and examines the variations in their patterns, which are consistent with a number of different functional explanations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hare et al (2002) 36 have argued that the process of domestication has also conveyed advanced socio-37 cognitive abilities to dogs (e.g., Hare selective breeding not only became increasingly tame and friendly toward humans, but 43 also developed a dog-like appearance with floppy ears, spotty coats and curly tails 44 (Belyaev et al 1981;Trut et al 2002). 45 One aspect of the dog-human affectional bond, often sited by pet-owners, is the 46 fact that dogs seem empathically well-tuned to human emotions (Vitulli 2006 however, systematic observational data on post-conflict "consolation" in apes (de Waal & 105 van Roosmalen 1979), rooks (Seed et al 2007) and domestic dogs (Cools et al 2008). 106…”
mentioning
confidence: 99%
“…Following Preston and de Waal's (19) discussion of the mechanisms and levels of empathy, consolation may represent an intermediate level that corresponds with ''sympathetic concern'' in developmental psychology (20). Monkeys seem to lack this particular level (21,22), but intriguingly, there is suggestive evidence for consolation in large-brained birds (23) and dogs (24).…”
mentioning
confidence: 99%